Factors which influence on force of boxers` and footballers` shots on the stage of base pre-treatment - Nikitenko S.A; Nikitenko A.O; Nikitenko A.A (Kharkov National Pedagogical University, 2011)
On the stage of base pre-treatment factors which influence on force of shots the hands of boxers and feet of footballers as a criterion of competition activity efficiency are certain. Connections are certain between force of shots by hands and feet. The objective test of the specialized sense determination of boxers` and footballers` shots is offered. It is recommended to develop maximal and explosive force of all parts of sportsman body at implementation preparatory exercises with the further transfer of physical qualities on implementation of the special exercises.